The Effect of Providing Biochar and Manure on Nutrient Uptake and Corn Yield In Alluvial Soil - Hayati, Rita; Agustine, Leony (Biofarm : Jurnal Ilmiah Pertanian, 2024)
Corn (Zea mays L.) in Indonesia is a plant that is often cultivated, this is because corn is the main alternative food substitute. This is what makes demand for corn production continue to increase. Realizing this, one effort that can be made is by cultivating corn plants on less than optimal land. Alluvial soil contains a lot of sand and clay, does not contain many nutrients. Several alternatives to overcome this problem, one of which is the provision of biochar and manure as soil amendments. The role of biochar in soil can be used as an indicator of soil quality, such as soil aggregate stability, retention and nutrient availability. Providing biochar can increase soil pH. Manure is fertilizer that comes from various kinds of livestock manure including: manure from cow manure, goat/sheep manure and chicken manure. Manure can improve physical properties by making the soil loose and loose so that aeration becomes better and is easier for plant roots to penetrate, improving the chemical properties of the soil through contributing nutrients to plants. Judging from the problems found in alluvial soil and the role of biochar and drum fertilizer, this research aims to determine the effect of providing biochar and manure on nutrient uptake and yield of corn plants in order to optimize corn cultivation. It is hoped that the results of this research can optimize corn cultivation on alluvial soil. The output of the research is expected to be published in the SINTA accredited national journal.